Collaborative interactions for medical e-diagnosis. (21st October 2008) - Fuin, D.; Garcia, E.; Guyennet, H.; Lapayre, J-C.
The Network and Distributed Systems Group within the University of Franche-Comte's computer research lab (LIFC) gained solid expertise on medical e-diagnosis in the area of remote collaboration through continued research and findings. TeNeCi (Cooperative Teleneurology) is a European remote diagnosis project applied to neurology developed under the aegis of INTERREGIII. INTERREGIII is a European Community Initiative program aiming at supporting cross-border, transnational and interregional co-operation in both social and economic perspectives. This paper has a dual objective: it first presents the improvements and contributions made to advance the TeNeCi project which is a research and development tool, and then it synthesises our research work in collaborative medical e-diagnosis. The TeNeCi tool originality is to allow practitioners to act as if they were at the same diagnosis table, using a great panel of medical tools (images, software, ...). Collaboration and awareness features are used to make TeNeCi more efficient than classical telemedicine software in terms of collaboration level.